ANALISIS PSIKOLOGI SASTRA NILAI PENDIDIKAN KARAKTER DALAM CERITA PENDEK LELAKI YANG MENDERITA BILA DIPUJI KARYA AHMAD TOHARI - Myatun Naimah; Yulia Puspasari; Fifin Aditha Putri Prastin; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2025)
Short stories are part of the story that provides character education so that moral values ​​can be derived. Short stories can be enjoyed reading in just one sitting. Many of Ahmad Tohari's short stories have been read and taken from stories of people's lives. The short story Men who suffer when they are praised is part of his work that can be analyzed using literary psychology. Praise given by the public sometimes gives an unpleasant impression to hear. Praise will be given if someone has made progress or made efforts to bring about good changes. But it is different from Mardanu in the short story, who will suffer with praise from other people. According to Freud, literary psychology is divided into id, ego, and superego. Apart from literary psychology, there are also educational values ​​that can be applied in society. The educational values ​​conveyed also include social values, responsibility, religion, discipline, hard work, and so on.